PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN PASIEN DI PUSKESMAS CIBITUNG KABUPATEN SUKABUMI - Engkus Engkus (Jurnal Governansi, 2019)
The main problem of Cibitung’s Community Health Center in Sukabumi Regency is the lack of service quality caused by human resources, facilities, and referrals that have not been optimal yet. The research aims to analyze the influence of service quality on patient satisfaction. The method of the research is the quantitative approach with associative method to analyze two variables, namely service quality and patient satisfaction. The results of the research indicate that the validity and reliability tests are valid and reliable with value of r table 0.195. The results of questionnaire data processing and the answers of respondents regarding service quality show the effective criteria 82.4%. The results of questionnaire data processing and the answers of respondents regarding patient satisfaction show the effective criteria 81.4%. The t test indicates that value of t > t table is obtained (11.955 > 1.988). It means that there is partially a significant influence of service quality on patient satisfaction, then Ho is rejected. The correlation analysis of R obtains 0.772, indicating that there is a strong relationship of service quality to patient satisfaction. The result of coefficient determination obtains R square score 0.596 or 59.6%, therefore the contribution percentage of service quality variable to patient satisfaction variable is 59.6%, included in the high effective criteria. The conclusion is that there is a strong influence of service quality on patient satisfaction in Cibitung’s Community Health Center of Sukabumi Regency.Keywords: Facilities, Patient Satisfaction, Service Quality.